2022
DOI: 10.1038/s41467-022-33780-1
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis of cribriform prostate cancer reveals cell intrinsic and tumor microenvironmental pathways of aggressive disease

Abstract: Cribriform prostate cancer, found in both invasive cribriform carcinoma (ICC) and intraductal carcinoma (IDC), is an aggressive histological subtype that is associated with progression to lethal disease. To delineate the molecular and cellular underpinnings of ICC/IDC aggressiveness, this study examines paired ICC/IDC and benign prostate surgical samples by single-cell RNA-sequencing, TCR sequencing, and histology. ICC/IDC cancer cells express genes associated with metastasis and targets with potential for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 116 publications
4
43
0
Order By: Relevance
“…Clusters were annotated with well‐known markers. The cells were classified into 16 major cell types (Figure 1C–E) including B cells marked by Cd79A , Cd79B , and Ms4a1 , [ 13 ] NKs marked by Ncr1 , Klrb1c , and Nkg7 , [ 14 ] macrophages marked by C1qb , Cd68 , Csf1r , and Mrc1 , [ 15 ] neutrophils marked by S100α9 , IL1β , and Csf3r , [ 16 ] monocytes marked by Ccr2 and Ly6c2, [ 17 ] T cells marked by Cd3d , Cd3e , and Cd247 , [ 18 ] pDCs marked by Cd209a and Cd74 , [ 19 ] mast cells marked by Fcer1a , Kit , and Ms4a2 , [ 20 ] erythroblasts marked by Ttr , Enpp2 , and Ptgds , erythrocyte marked by Car2 , Hba‐a1 , and Hbb‐bs , [ 21 ] mesenchymal cells marked by Col1a1 , Col1a2 , Col3a1 , and DCN , [ 13 ] epithelial cells identified by the expression of Birc5 and Ube2c , [ 22 ] endothelial cell marked by Pecam1 , Cdh5 , and Kdr , [ 13 ] forebrain neuron marked by Gng13 and S100α5 , [ 23 ] glial cell marked by S100b and Cdh2 , [ 24 ] and neuralprecursor cells marked by Cdh2 , Pde6g , and Gnb3 . [ 24 ] Although all 16 major cell types were presented in mLVs both in sham and SAH groups (Figure 1C), the dynamic changes of each cell type were different.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters were annotated with well‐known markers. The cells were classified into 16 major cell types (Figure 1C–E) including B cells marked by Cd79A , Cd79B , and Ms4a1 , [ 13 ] NKs marked by Ncr1 , Klrb1c , and Nkg7 , [ 14 ] macrophages marked by C1qb , Cd68 , Csf1r , and Mrc1 , [ 15 ] neutrophils marked by S100α9 , IL1β , and Csf3r , [ 16 ] monocytes marked by Ccr2 and Ly6c2, [ 17 ] T cells marked by Cd3d , Cd3e , and Cd247 , [ 18 ] pDCs marked by Cd209a and Cd74 , [ 19 ] mast cells marked by Fcer1a , Kit , and Ms4a2 , [ 20 ] erythroblasts marked by Ttr , Enpp2 , and Ptgds , erythrocyte marked by Car2 , Hba‐a1 , and Hbb‐bs , [ 21 ] mesenchymal cells marked by Col1a1 , Col1a2 , Col3a1 , and DCN , [ 13 ] epithelial cells identified by the expression of Birc5 and Ube2c , [ 22 ] endothelial cell marked by Pecam1 , Cdh5 , and Kdr , [ 13 ] forebrain neuron marked by Gng13 and S100α5 , [ 23 ] glial cell marked by S100b and Cdh2 , [ 24 ] and neuralprecursor cells marked by Cdh2 , Pde6g , and Gnb3 . [ 24 ] Although all 16 major cell types were presented in mLVs both in sham and SAH groups (Figure 1C), the dynamic changes of each cell type were different.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis showed that PSMA-TV is higher for the cribriform histotype and lower for the acinar histotype. The incidence of a cribriform pattern is about 25–34% of prostate biopsies [ 37 ]. It is important to report the cribriform morphology due to its impact on patient management.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well known that the cribriform pattern is correlated with a higher BCR rate and associated with a higher metastatic risk. Hong Yuen Wong et al [ 37 ] demonstrated that there is a specific interaction between the cancer cells in the cribriform pattern and the tumoral microenvironment; they showed the presence of MYC-induced genes’ upregulation and a strong enrichment of TNFa signaling. There is also a higher expression of SCHLAP1, a long non-coding RNA associated with the progression to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The scRNA-seq data related to PCa were downloaded from GSE141445, [16] GSE157703, [19] and GSE185344 [18] via the Gene Expression Omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/). After excluding 4 samples from metastatic patients and 2 samples that lacked fibroblasts, a total of 7 samples were included from GSE141445.…”
Section: Methodsmentioning
confidence: 99%